LEARNER’S LEXICOGRAPHY AS A USER-CENTERED FIELD OF LEXICOGRAPHY - Anna GOLYNSKAIA (Fırat University, 2019)
Learner’s lexicography comprises dictionaries prepared for those who learn a foreign language at an intermediate or upper level. The peculiar feature of leaner’s dictionaries is that they include information in accordance with the learners’ needs, their psychological characteristics, age and stage of learning. Even “Divânü Lugât'it-Türk”, which is said to be the first dictionary of Turkish, pursued a pedagogic goal; it was aimed at teaching Turkish to Arabs. Despite the fact that learner’s lexicography, which occupies a distinct and valued place in contemporary lexicography, has a lot to offer to a researcher, it is still an unexplored field in Turkey. The aim of our paper is to attract attention to learner’s lexicography, which hasn’t taken its place in Turkish scientific literature yet, and to present theoretical studies done in this field. Our research puts forward the historical past of learner lexicography and reveals the basic concepts and principles related to this field. Learner’s dictionaries, which emerged in the first half of the 20th century due to the work of such linguists and educators as Edward L. Thorndike, Harold Palmer, Michael West and A.S. Hornby, had passed through many stages before they acquired their present state. In our work, learner lexicography is treated as a subset of pedagogical lexicography. Learner’s dictionaries are human-centered and help learners to learn a foreign language and use it effectively. According to their main characteristics, learner’s dictionaries can be divided into three groups: monolingual, bilingual and bilingualised dictionaries. In our research, the strengths and weaknesses of the above-mentioned dictionaries were examined and the effects on the foreign language learning/teaching process were discussed.